Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Aparatur Sipil Negara - Alfarizi, Farid; Nur, Irawati; Nurbaki, Rezky; Anggerwati, A. Indah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This research aims to determine and discover the relationship between organizational culture and work environment variables on employee performance at the Parepare City Environmental Service Office, both partial and simultaneous relationships. The analytical methods used in this research are Multiple Linear Regression Analysis, Validity Test, Reliability Test, Partial Test (t test), Simultaneous Test (F test) and Determination Coefficient Test (R2 test) with a sample of 35 respondents.The research results show that organizational culture (X1) has a positive and partially significant influence on the performance (Y) of employees at the Parepare City Environmental Service Office, with a t-count value of 2.616 > t-table 2.042 and a significant value of 0.014 < 0.05 . The work environment (X2) has a positive and partially significant influence on the performance (Y) of employees at the Parepare City Environmental Service Office, with a calculated t-value of 4.046 > t table 2.042 and a significant value of 0.000 < 0.05. The variables organizational culture (X1) and work environment (X2) have a positive and significant effect simultaneously on employee performance at the Parepare City Environmental Service Office, with an F-count value of 16.897 > F-table 3.31 and a significant value of 0.000 < 0, 05.